Enhanced electrocatalytic activity via phase transitions in strongly correlated SrRuO3 thin films. Issue 4 (4th April 2017) - Lee, Sang A; Oh, Seokjae; Hwang, Jae-Yeol; Choi, Minseok; Youn, Chulmin; Kim, Ji Woong; Chang, Seo Hyoung; Woo, Sungmin; Bae, Jong-Seong; Park, Sungkyun; Kim, Young-Min; Lee, Suyoun; et al.
Abstract : The electronic structure of a strongly correlated SrRuO3 epitaxial thin film influences the electrocatalytic activity significantly. Abstract : Transition metal oxides have been extensively studied and utilized as efficient catalysts. However, the strongly correlated behavior which often results in intriguing emergent phenomena in these materials has been mostly overlooked in understanding the electrochemical activities. Here, we demonstrate a close correlation between the phase transitions and oxygen evolution reaction (OER) in strongly correlated SrRuO3 . By systematically introducing Ru–O vacancies into the single-crystalline SrRuO3 epitaxial thin films, we induced a phase transition in crystalline symmetry which resulted in the corresponding modification of the electronic structure. The modified electronic structure significantly affects the electrochemical activities, so a 30% decrease in the overpotential for the OER activity was achieved. Our study suggests that a substantial enhancement in the OER activity can be realized even within single material systems, by rational design and engineering of their crystal and electronic structures.